Analysis of The Causes of The Decline in Profits of The Bank Tabungan Negara (Persero) Tbk 2019 - Girang Permata Gusti; Rudi Triadi Yuliarto (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2020)
The purpose of this study was to determine the main cause of the decline in profits of PT. Bank Tabungan Negara (Persero) in 2019. The research method used in this research is descriptive, this method serves to reveal a systematic picture and gather every available fact. This study uses quantitative data types, in the form of secondary data obtained from the company's annual financial statement documentation for ten years, starting from 2010 to 2019. The company's financial statements are presented, then analyzed and interpreted thoroughly and in detail. There are seven ratios or indicators of financial performance that the authors have chosen to be used as a reference and to measure the causes of the company's financial performance decline. The results of the study concluded that the increase in problem loans was the cause of the company's net profit in 2019 to fall to 92.5% from 2.8 trillion rupiahs in 2018 to only 209.26 billion rupiahs.